Matematyka

Autorzy:Aleksandra Ciszkowska, Alina Przychoda, Zygmunt Łaszczyk

Wydawnictwo:WSiP

Rok wydania:2012

Zauważ, że (√3-1)²= 4-2√3. Zatem 4.57 gwiazdek na podstawie 7 opinii
  1. Liceum
  2. 1 Klasa
  3. Matematyka

`sqrt(9-4sqrt5) \ \ \ stackrel(a^2-2ab+b^2=(a-b)^2)=\ \ \=sqrt(4-4sqrt5+5)=sqrt(2^2-2*2*sqrt5+(sqrt5)^2)=sqrt((2-sqrt5)^2)=`

`=stackrel"(-)"|2-sqrt5|=-2+sqrt5=sqrt5-2`

 

 

`sqrt(46+6sqrt5) \ \ \ stackrel(a^2+2ab+b^2=(a+b)^2)=\ \ \ sqrt(1+6sqrt5+45)=sqrt(1^2+2*1*sqrt5+(3sqrt5)^2)=`

`=sqrt((1+3sqrt5)^2)=stackrel"(+)"|1+sqrt5|=1+sqrt5`

 

 

`sqrt(16-6sqrt7) \ \ \ stackrel(a^2-2ab+b^2=(a-b)^2)=\ \ \ sqrt(9-6sqrt7+7)=sqrt(3^2-2*3*sqrt7+(sqrt7)^2)`

`=sqrt((3-sqrt7)^2) =|3-sqrt7| \ \ \ stackrel(sqrt7<sqrt9 \ \=> \ \ sqrt7<3)=\ \ \stackrel"(+)"|3-sqrt7|=3-sqrt7`